Perbandingan Volatilitas Asimetris Saham Bertanggung Jawab Sosial danSaham Konvensional di Indonesia Selama Pandemi Covid-19 Periode 2020-2021 - Misbahuddin, Muhammad Rizki; Adawiyah, Wardatul (Jurnal Manajemen dan Usahawan Indonesia, 2022)
This study aims to examine the asymmetric volatility of socially responsible stocks and compare it with conventional stocks during the COVID-19 pandemic in Indonesia. The research used asymmetric volatility modelling with the GJR-GARCH model to detect the presence of a leverage effect in the sample which consisted of one index and 20 socially responsible stocks and 21 indices and 34 conventional stocks. The data used is compiled from Thomson Eikon Reuters and Tradingview with a data collection period of January 1, 2020 to December 31, 2021. The results of the study found that there was a significant leverage effect on the SRI-KEHATI index. However, there is no significant leverage effect on socially responsible stocks at the individual level. The study also found that the socially responsible stock index had a higher leverage effect value than the majority of conventional indices in the research sample. The results of this study suggest for investors to choose socially responsible stocks more carefully if the purpose of adding these socially responsible stocks is to reduce risk in their investment portfolios during the COVID-19 pandemic.